2008
DOI: 10.1002/pssa.200723608
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of thin ferrite films on silicon using RF sputtering

Abstract: Thin‐films of Nix Zn1–x Fe2O4 [(Ni,Zn)‐ferrite] are grown by means of RF sputtering on Si(100) and (111) substrates, corresponding to the orientation of Si cantilevers for AFM/MFM measurements. We find that the ferrite can be sputtered directly onto the Si surfaces, but an additional annealing step is required to obtain a purely polycrystalline, soft magnetic film. The microstructure of the films is investigated employing transmission electron microscopy, electron backscatter diffraction and magnetic force mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The resulting ferrite film is polycrystalline, with a nearly random orientation of the individual ferrite grains. The TEM-determined grain sizes range between 5 and 20 nm, which is too small for an electron backscatter diffraction analysis as performed in [7] on a 100-nm-thick NiZnFe 2 O 4 film. Nevertheless, the random orientation of the grains is similar to that of the much thicker NiZnFe 2 O 4 film.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting ferrite film is polycrystalline, with a nearly random orientation of the individual ferrite grains. The TEM-determined grain sizes range between 5 and 20 nm, which is too small for an electron backscatter diffraction analysis as performed in [7] on a 100-nm-thick NiZnFe 2 O 4 film. Nevertheless, the random orientation of the grains is similar to that of the much thicker NiZnFe 2 O 4 film.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting ferrite coatings had thicknesses of typically 50 up to 100 nm. For the NiZnFe 2 O 4 ferrite, we found that a slow cooling stage after the annealing in air leads to an enhanced grain growth [7]. For both ferrites, polycrystalline ferrite grains are obtained without any amorphous ferrite layer located at the Si substrate.…”
Section: Introductionmentioning
confidence: 94%
“…It shows that all the samples are well-crystallized and single-phase with spinel crystal structure. Observation of only selected peaks is seen in all the samples which usually appear in ferrite films [15,31]. It is worth noting that with the increase of P Ar : PO 2 the (311) peak shifts to a larger diffraction angle and its width becomes narrow.…”
Section: Ni-zn Ferrite Thin Filmsmentioning
confidence: 98%
“…Ni-Zn ferrite thin films which have the highest 4M s in ferrites were investigated. To our knowledge, the soft ferrite films deposited by many methods [12][13][14][15][16][17] require high temperature post-heating treatments or substrate heating at least of 600°C to obtain a better spinel structure and soft magnetic properties, which is impossible for electronic circuit integrations. We report the achievement the in-situ fabrication of Ni-Zn ferrite films with well-defined spinel crystal structure at room temperature without any heating treatments by magnetron sputtering [18,19].…”
mentioning
confidence: 99%
“…However, thick ferrite deposition is still challenging on silicon wafers. RF sputtering [8] and PLD (pulsed laser deposition) [9] processes have been used to deposit ferrite, but deposition and deposition area are limited to low rate and small area.…”
Section: Introductionmentioning
confidence: 99%